Ovarian follicular dynamics and uterine changes during the ovulatory wave predicts imminent ovulation in Mares - Ararsa Duguma; Alemayehu Lemma (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Equine reproduction is unique by having long behavioral estrus and variations in ovarial follicular dynamics that made difficulty to standardize breeding time in mares. There are limited data on equine reproduction and breeding in Ethiopia. An experimental study was conducted at Balderas sport horses and recreational center, Addis Ababa, Ethiopia to determine ovarian follicular dynamics in local and exotic cross breed mares. A daily transrectal ultrasonography was carried out to evaluate uterine changes and ovarian structures for 2 consecutive estrus cycles, as well as teasing scores estimated during estrus. The mean (±SEM) of cross sectional uterine diameter were 44.4±0.5mm and 45±0.5mm for local and cross breed mares respectively; whereas scores of endometrial fold was 3.1±0.1 in local and 2.8±0.1 in cross breed mares with significant difference at P < 0.05. The mean (±SEM) diameter of preovulatory follicle for local and cross breed mares were 49.1±1.0mm and 50.1±0.8mm, respectively.Length of estrus was 7.0±0.9 days for local and 6.1±0.6 days for cross breed mares. Fast growth of dominant follicles in cross breed shorten interovulatory interval than local breed mares.A positive correlation of teasing scores, uterine diameter and endometrial fold with diameter of preovulatory follicles (r=0.5) in the present study has been used to estimate imminent ovulation.Ovulation occurred within 6-7days of mean scores of 2.8-3.1endometrial fold, 44.4-45mm of uterine diameter and 2-4 teasing scores for both mares.In conclusion, imminent ovulation can be predicted by measuring uterine diameter, scoring endometrial fold and considering teasing scores in relation to diameter of preovulatory follicles when breeding mares.